PERANCANGAN TRAFFIC LIGHT BERBASIS MICROCONTROLLER ATMEGA 16 - Alfith Alfith (Jurnal Momentum ISSN 1693-752X)
Today, the highway as a means to facilitate transport often have problems, caused by all road users desire more quickly to the destination, and precede each other, plus more if there is a special car or a group, it is very influential on the impact on the density of traffic congestion . To address them, in fact is not the duty of the police to regulate the traffic, but we can help to regulate traffic in any place such as a T-junction, intersection, or perlimaan densely trafficked rate traffic arrangements necessary tool called the Traffic Light. This is the basis for "Traffic Light Design Based Microcontroller ATmega 16". The traffic light is able to overcome some of the perceived problems, including traffic lights remain lit seek even suply of PLN outages by using backup batteries. The system is able to regulate the rate of traffic by arranging road vehicles alternately passing a certain place every day for almost 24 hours a day and on the tool needs to be paired each day.